2017
DOI: 10.1016/j.kint.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Improved clinical trial enrollment criterion to identify patients with diabetes at risk of end-stage renal disease

Abstract: Design of Phase III trials in diabetic nephropathy currently requires patients at high risk of progression defined as within three years of a hard end-point (end stage renal disease, 40% loss of estimated glomerular filtration rate, or death). To improve design of these trials, we used natural history data from the Joslin Kidney Studies of chronic kidney disease in patients with diabetes to develop an improved criterion to identify such patients. This included a training cohort of 279 patients with type 1 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…19 The strong association of TNFRs with the risk of ESRD was replicated in our subsequent studies of T1D 43 and T2D. 44 Similar results were found in Pima Indian T2D, including a lack of association between serum levels of TNFα and risk of ESRD. 45 Our findings were confirmed recently in other populations.…”
Section: Mechanisms Underlying Renal Decline In Diabetessupporting
confidence: 61%
See 1 more Smart Citation
“…19 The strong association of TNFRs with the risk of ESRD was replicated in our subsequent studies of T1D 43 and T2D. 44 Similar results were found in Pima Indian T2D, including a lack of association between serum levels of TNFα and risk of ESRD. 45 Our findings were confirmed recently in other populations.…”
Section: Mechanisms Underlying Renal Decline In Diabetessupporting
confidence: 61%
“…In our recent study, Yamanouchi et al sought to develop criteria to identify fast decliners among diabetic patients with chronic kidney disease (CKD stages 3 or 4), so they could be enrolled into clinical trials. 44 Toward this end, we examined baseline and follow-up data from patients enrolled into the T1D Joslin Proteinuria Cohort. A similar cohort of patients with T2D was used as a validation cohort.…”
Section: How To Diagnose Fast Decliners?mentioning
confidence: 99%
“…Further analysis of this trial utilized an established marker of chronic kidney disease, serum levels of soluble tumor necrosis factor receptor 1 (sTNFR1), to determine which patients were most at risk of progression to end stage renal disease. It was found that 51% of patients had a serum baseline level of sTNFR1 > 4.3 ng/mL (Tarrant et al, 2018), indicating that they were at high risk of progression (Yamanouchi et al, 2017). This subgroup of patients had an apparent therapeutic benefit from selonsertib 18 mg compared to placebo when comparing eGFR chronic slope (WK4 to WK48) difference (p = 0.029) (Tarrant et al, 2018).…”
Section: Ask1 Inhibition In Chronic Kidney Diseasementioning
confidence: 99%
“…A scientific workshop sponsored by the National Kidney Foundation and the US FDA concluded that a confirmed decline in eGFR of 30% over 2-3 years may be a valuable alternative surrogate end point for CKD progression in most circumstances [139]. Another challenge is to improve clinical trial enrolment criterion to identify T2DM patients at higher risk of ESRD [140]. This improvement will be crucial to reduce the sample size and ameliorate the statistical power by increasing the number of key events in RCTs.…”
Section: Expert Opinionmentioning
confidence: 99%